Profile evaluation of orthodontic professionals as for their legal actions - Paranhos, Luiz Renato; Salazar, Marcio [UNESP]; Torres, Fernando César; Pereira, Antônio Carlos; da Silva, Rhonan Ferreira [UNESP]; Ramos, Adilson Luiz (FapUNIFESP (SciELO), 2011)
Objective: Evaluate the legal actions and behavior in the doctor/patient relationship, used by dental surgeons practicing orthodontics. Methods: The population sample of the present study consisted of dental surgeons, active in the field of orthodontics, and registered with Dental Press Publishing Company - Maringá/PR, Brazil, with a total sample size of 525 professionals. The research was conducted using a 17-question survey forwarded to these professionals. Results and Conclusions: The majority of participants in our study are specialized in orthodontics; 75% of professionals use some sort of contract at the office/clinic; 73.7% of professionals periodically request maintenance X-rays; a large percentage of professionals (58.9%) keep patient records on file for life. The interviewed professionals demonstrate good knowledge of the Brazilian Code of Ethics in Dentistry, especially of Chapter XIV - on Communication.
Keywords: Enacted statutes; Legal liability; Orthodontics; Professional practice